Gut microbiota links to histological damage in chronic HBV infection patients and aggravates fibrosis via fecal microbiota transplantation in mice - Fengjiao Wang; Yechen Wu; Jiali NI; Qianhan Xie; Jian Shen; Hui Chen; Chengyu Ma; Yuanyuan Yao; Jinzhi Wang; Lvwan Xu; Qiangqiang Xiang; Yuxi Zhao; et al. (Microbiology Spectrum)
ABSTRACT Gut microbiota dysbiosis has been observed in HBV-related cirrhosis, but its role in early-stage disease and its correlation with liver pathology remain unclear. Moreover, whether dysbiosis is a cause or consequence of liver cirrhosis is still debated. We recruited 20 treatment-naïve patients with chronic HBV infection, assessing liver injury via biopsy. Fecal metagenomic sequencing was used to analyze the correlation between gut microbiota and liver histology. To explore the causality, fecal samples from an HBV-related cirrhosis patient were transplanted into mice with CCl₄-induced liver fibrosis. Patients with significant histological damage exhibited reduced alpha diversity and greater microbial homogeneity. Species such as Eubacterium_sp_CAG_180, Gemmiger_formicilis, and Oscillibacter_sp_ER4 had decreased abundance, while Parabacteroides_distasonis, Bacteroides_dorei, and Bacteroides_finegoldii were enriched. Mice receiving fecal transplants from the cirrhotic patient showed aggravated liver fibrosis, with increased collagen deposition; elevated ALT, AST, and ALP levels; and heightened hepatic inflammatory gene expression. Additionally, abnormal bile acid profiles with elevated unconjugated bile acids (e.g., GCA and CA) were observed. Gut microbiota dysbiosis is closely associated with liver histological damage in chronic HBV infection and may drive fibrosis progression via microbial-bile acid interactions. These findings suggest potential for gut microbiota-based assessment and treatment strategies in chronic hepatitis B.IMPORTANCEThis study elucidates a significant association between gut microbiota dysbiosis and liver histological damage in patients with chronic hepatitis B (HBV), potentially exacerbating fibrosis progression through bile acid interactions. By analyzing patient gut microbiota and conducting fecal transplant experiments in mice, researchers have identified that gut microbiota dysbiosis contributes to hepatic fibrosis during chronic HBV infection. These findings underscore the importance of the gut-liver axis in HBV disease progression, indicating that monitoring or modulating gut bacteria may facilitate early diagnosis or therapeutic interventions. This research bridges the gap in understanding whether microbial alterations drive disease progression or result from it, providing a foundation for developing therapies targeting the microbiome to mitigate liver damage in chronic HBV infections.